Дослідження актопротекторної активності похідних 4-R-3-(морфолінометилен)-1,2,4-тріазол-5-тіолу - Щербина, Роман Олександрович; Капелянович, Є. В.; Пругло, Євген Сергійович; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Shcherbyna, R. O.; Kapelyanovych, Ye. V.; Pruglo, Ye. S.; Panasenko, O. I.; Knysh, Ye. H. (My University, 2014)
Excessive physical and neuro-psychological overload causing changes in physiological and mental condition of the employee, which lead to the development of fatigue and overwork. Exhaustion is a combination of stable unfavorable for workers health functional changes in the body, which significantly reduce productivity and can cause injury in the workplace. Thus, the search for new biologically active compounds with a strong actoprotective properties are important for modern medicine. The purpose of our studies was to investigate the actoprotective properties of some derivatives of 4-R-3-(morpholinomethylene)-1,2,4-triazole-5-thiole and detection of some regularities according to pharmacological activity and the chemical structure of synthesized compounds. For studying the actoprotective effect of new derivatives of 1,2,4-triazole, and determine the resistance effect of experimental animals to extreme conditions the “forced swimming model” was used. In accordance with the methodology the Inosin (Riboxin) was used as the reference drug. As a result of the research it was found that two compounds (PKR-127 and PKR-131) demonstrated tendency to actoprotective activity, with strength which exceeded referent drug. Some regularities of the influence structure of tested substances for the pharmacological activity were established, and they can be useful in future for searching highly effective actoprotective drugs.
The studing of actoprotective action of 4-R-3-(morpholinomethylene)-1,2,4-triazole-5-thiole derivatives
Keywords: derivatives of 1,2,4-triazole; actoprotective action; fatigue